The implications of AI tools on educational practices - Ahmad, Irma; Mokhtar, Norashikin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In recent years, generative AI models have captured global attention for their impressive ability to create content that mimics human output. One such tool, ChatGPT, has gained popularity in educational settings. These technologies offer support to both educators and learners in areas such as problem-solving, question answering, and academic writing, as they can boost students’ motivation, deepen understanding of complex subjects, and support skill development. The integration of AI not only benefits educators and learners but also plays a transformative role in four core areas of education learning, teaching, assessment, and administration reshaping the educational landscape.